2003
DOI: 10.1002/hlca.200390262
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Formation of a 14‐Membered Cyclodepsipeptide

Abstract: The treatment of diluted solutions of the hydroxy diamides 6a and 6b in toluene with HCl gas at 100°gave the dimeric, 14-membered cyclodepsipeptide 10 in up to 72% yield (Scheme 3). The same product was formed from the linear dimer of 6b, the depsipeptide 11, under the same conditions (cf. Scheme 4). All attempts to prepare the cyclic seven-membered monomer 9, starting with different precursors and using different lactonization methods failed, and 10 was the only product which was isolated (cf. Scheme 6). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Effective methods for the introduction of α,α-disubstituted α-amino acids and subsequent ring closure to give a cyclic depsipeptide are therefore of interest. A useful cyclization method for depsipeptides containing a C-terminal α,α-disubstituted α-amino acid, the so-called 'direct amide cyclization' method, has been developed in our laboratory [9][10][11][12][13][14][15][16][17][18][19][20]. The basic concept is shown in Scheme 1: if an amide of type 1 is treated with dry HCl-gas, the corresponding 1,3-oxazol-5(4H)-one derivative 2 is formed via ring closure and elimination of dimethylamine hydrochloride.…”
mentioning
confidence: 99%
“…Effective methods for the introduction of α,α-disubstituted α-amino acids and subsequent ring closure to give a cyclic depsipeptide are therefore of interest. A useful cyclization method for depsipeptides containing a C-terminal α,α-disubstituted α-amino acid, the so-called 'direct amide cyclization' method, has been developed in our laboratory [9][10][11][12][13][14][15][16][17][18][19][20]. The basic concept is shown in Scheme 1: if an amide of type 1 is treated with dry HCl-gas, the corresponding 1,3-oxazol-5(4H)-one derivative 2 is formed via ring closure and elimination of dimethylamine hydrochloride.…”
mentioning
confidence: 99%
“…A correction for secondary extinction was applied. Refinement of the absolute structure parameter [19][20] yielded a value of 0.01 (6), which confirms that the refined model represents the true absolute structure. Neutral atom scattering factors for non-H atoms were taken form [21] and the scattering factors for H-atoms were taken from [22].…”
Section: -(5-chloro-33-dimethylpentanoylamino)-2-methylpropanoic Acmentioning
confidence: 77%
“…Recently, we have shown that diamides of type A, which contain β-hydroxy acids, i.e. 1 (n = 2), under these reaction conditions did not give the expected 7-membered cyclodepsipeptides, and only their dimers, the 14-membered rings 4 were isolated in good yields [6][7] (Scheme 2). Treatment of γ-hydroxy acid derivatives (1, n = 3) with HCl gas in toluene yielded no cyclodepsipeptides at all.…”
Section: Methodsmentioning
confidence: 99%
“…A useful method for the introduction of such amino acids into peptides is the so-called 'azirine/oxazolone method' [1], which proved to be a convenient preparative access to such peptides. This strategy has been applied extensively in the synthesis of linear oligopeptides [2][3][4][5][6][7][8], endothiopeptides [9][10][11][12][13], conformationally restricted cyclic peptides [14][15][16][17], and cyclic depsipeptides [17][18][19][20][21][22][23][24][25][26] containing 2,2-disubstituted glycines.…”
mentioning
confidence: 99%